Subcellular localization of the Rhizobium leguminosarum nodI gene product. - Schlaman, H R (1990)
By the use of antibodies raised against a fusion protein of lacZ'-nodI (produced in Escherichia coli) which specifically react with NodI protein, it was shown that in wild-type Rhizobium leguminosarum biovar viciae NodI protein (i) is recovered with the cytoplasmic membrane fraction and (ii) is translated as part of the nodABCIJ operon. In addition, it was found that the bacterial chromosomal background strongly influences the expression of several nod genes.